Measuring the patient safety climate in community pharmacies: an updated national survey - Christina Ljungberg Persson; Annika Nordén Hägg; Björn Södergård (BMJ Open)
Background The patient safety climate in community pharmacies was measured nationally in Sweden in 2008. Since that time the Swedish pharmacy market has undergone a re-regulation which probably has affected the patient safety climate in pharmacies.Objectives The aim was to evaluate the patient safety climate among pharmacists working in Swedish community pharmacies and compare it with historical data.Design The patient safety climate among pharmacists was analysed in two cross-sectional surveys. Historical data from 2008 and data collected in 2022 were compared. The Safety Attitudes Questionnaire (SAQ), containing items on safety culture arranged in six dimensions, was used in both surveys. It uses a 5-point Likert scale to create a quantitative description of the respondents’ perception of patient safety climate.Setting Community pharmacies in Sweden.Participants These surveys were census studies because all pharmacists working in community pharmacies in Sweden were invited to participate and no sampling occurred.Results The number of respondents was 2738 in 2008 and 1931 in 2022. The patient safety climate in Swedish community pharmacies appears to have worsened between 2008 and 2022 according to the pharmacists. All values of the dimensions included in the SAQ have decreased, except for the dimension of Stress Recognition, where an increase indicated a larger awareness among the pharmacists of how stress impacts their work. The overall negative trend in SAQ values seen between 2008 and 2022 was consistent, irrespective of the respondent’s level of education, their role in the pharmacy or the number of years since their education was completed.Conclusions The patient safety climate in community pharmacies in Sweden seems to have deteriorated. With an increasingly strained healthcare system, community pharmacists must be reliable defenders of patient safety, and it is essential to ensure that the climate in their workplace supports the important work being carried out.